2014
DOI: 10.7314/apjcp.2014.15.18.7955
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs1219648 in FGFR2 and rs1042522 in TP53 with Premenopausal Breast Cancer in an Iranian Azeri Population

Abstract: Breast cancer is the most common cancer among women in the world. In Iran, the incidence of breast cancer is on the increase. We here studied the association of rs1219648 in FGFR2 and rs1042522 in TP53 and their interaction in development of early onset sporadic breast cancer in Iranian Azeri population to evaluate epistatic effects on the risk of mammary neoplasia. We genotyped the two polymorphisms in 100 women with early onset breast cancer and 100 healthy women by PCR-RFLP. Allele frequency differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…The meta-analysis study suggested that HLA-G 14-bp InDel polymorphism might contribute to breast cancer susceptibility and overall cancer risk among Asians (Yz et al, 2014). In Azeri population of Iran located north western Iran, There is growing study performed that tried to access the association between some polymorphisms and breast cancer Saadatian et al, 2014;Sedaie et al, 2014). Until, in this population there is no report on HLA-G polymorphisms in breast cancer.…”
Section: -Bp Insertion/deletion Polymorphism Of the Hla-g Gene In Bmentioning
confidence: 99%
“…The meta-analysis study suggested that HLA-G 14-bp InDel polymorphism might contribute to breast cancer susceptibility and overall cancer risk among Asians (Yz et al, 2014). In Azeri population of Iran located north western Iran, There is growing study performed that tried to access the association between some polymorphisms and breast cancer Saadatian et al, 2014;Sedaie et al, 2014). Until, in this population there is no report on HLA-G polymorphisms in breast cancer.…”
Section: -Bp Insertion/deletion Polymorphism Of the Hla-g Gene In Bmentioning
confidence: 99%
“…For further studies, TP53 (rs1042522) polymorphism may be associated with other genetic factors because p53 interacts with various proteins that play role in programmed cell death 5,9 . For instance, it has been evaluated that some fibroblast growth factor receptor 2(FGFR2) gene polymorphisms are 3 0 associated with breast cancer and FGFR2 gene accomplishes its function in a p53-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been evaluated that some fibroblast growth factor receptor 2(FGFR2) gene polymorphisms are 3 0 associated with breast cancer and FGFR2 gene accomplishes its function in a p53-dependent manner. Activation of apoptosis is stimulated by interaction between FGFR2 and TP53 5 . Other genes synthesizing proteins that control cell cycle such as cyclins, cyclin-dependent kinases and p21 protein as a cyclin-dependent kinase inhibitor 1 can also be correlated with breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key characteristic of a systematic review is a comprehensive search to find eligible studies. This study has been conducted between 2007 and 2014, however, one study has been missed 2. According to the date of publication, a study published in 2015 has also been missed 3.…”
mentioning
confidence: 99%